Petrography and geochemical characterization of a granite batholith in Idanre, southwestern Nigeria - Akinola, Oluwatoyin O.; Azman A. Ghani,; James, Elvaene (Penerbit Universiti Kebangsaan Malaysia, 2021)
Idanre granite batholith in southwestern Nigeria contain three rock types, namely, Older granite undifferentiated (OGu), Older granite porphyritic (OGp) and Older granite fine-grained (OGf). The granitoids intruded into a basement rock of primarily migmatite gneiss. Petrography indicates that quartz, orthoclase, hornblende, and biotite are common to all members while microcline is more prominent in OGp and plagioclase is poorly represented in OGf. Despite minor differences in petrographic features, the granite units generally have similar geochemical relationships. The average SiO2 contents in OGp (70.49%), OGu (68.7%) and OGf (65.8%) are comparable to similar Pan-African suites located in eastern and northern Nigeria. Na2O+K2O-CaO versus SiO2 diagram shows all the granite members are calcic, K2O vs SiO2 plot classify the granites as high-K calcic alkali to shoshonitic. ANK vs ACNK plot indicates they are peraluminous. Plot of A/CNK vs SiO2 and K2O vs Na2O diagrams classified the rock as S-type granite. The granitoids are calc-alkaline with elevated Na2O (>2.6%) and Al/(Na2O+CaO) contents (OGu, 2.1-3.4; OGp, 2.4-3.1 and OGf, 2.2-2.9). The tectonic diagram (Rb vs (Y+Nb) indicates that the batholith is Within Plate Granite (WPG).